Surface engineering of polymeric substrates using plasma technique and applications - Sun, Ye (Nanyang Technological University, 2022)
Superhydrophobic/superhydrophilic surface functionalization has been drawing much attention recently especially on polymeric materials. Polymers enjoy certain unique advantages such as light weight, low cost, and good flexibility, making them a favorable choice for a wide range of industrial applications. On the other hand, the surface properties of polymers may not be suitable for some specific applications, especially when extreme wetting states (e.g., superhydrophilic, superhydrophobic) are required. Therefore, it is necessary to modify the inert polymer surface without affecting the properties of the bulk to meet the performance requirements of different applications. Despite the fact that many methodologies have been explored to modify the surface to be superhydrophobic or superhydrophilic, many of them are not suitable for heat sensitive polymer materials. Additionally, the mechanical durability of modified surface is still a main challenge faced by many practical applications.